Cleaning in the 21st Century: The musculoskeletal disorders associated with the centuries-old occupation – A literature review. (November 2022) - Lin, Jia-Hua; Lee, Wonil; Smith, Caroline K.; Yragui, Nanette L.; Foley, Michael; Shin, Gwanseob
Abstract: Workers performing cleaning duties experience higher injury rates, especially in the form of musculoskeletal disorders (MSDs), than other industries. It is essential to understand the inherent risks associated with the nature of this occupation. Based on the Balance Theory (Smith & Carayon-Sainfort, 1989), this review surveys the current literature, especially those published since the previous review paper (Kumar & Kumar, 2008), and identifies which elements contributing to MSD risks were examined: task, technology, organization, environment, individual, and their interactions. Thirty-nine research papers published between 2005 and 2021 are identified and summarized. Among these papers, task and individual elements received the most attention, at 42 and 34 occurrences, respectively. The interaction elements of technology-organization, technology-environment, and organization-environment received less than three mentions. The goal of this literature review is to update the knowledge base and identify current trends for the cleaning occupation. Possible interventions for risk reduction and future research directions are suggested. Highlights: Cleaners have a higher musculoskeletal disorder (MSD) rate than the average worker. Recent literature is reviewed based on the Balance Theory of MSD causation model. Studies mostly examined task, technology, and individual factors. Systematic evaluations of the cleaning occupation is recommended to address MSD risks.